Analgesic Effects of Triterpenoid Saponins From Stauntonia chinensis via Selective Increase in Inhibitory Synaptic Response in Mouse Cortical Neurons - Chen, Su; Rong, Yi; Liu, Mengxue; Cheng, Song; Liu, Xiangming; Li, Xiaohong; Yu, Yi; Yang, Guangzhong; Yang, Xiaofei (Frontiers in Pharmacology, 2018)
Triterpenoid saponins from Stauntonia chinensis (TSS) are potential therapeutic agents because of its analgesic properties. However, the underlying mechanisms of the anti-nociceptive activity of TSS are largely unclear, especially in CNS. The present study confirmed the analgesic effect of TSS using four models of acute pain based on thermal or chemical stimuli. TSS treatment specifically impaired the threshold of thermal- and chemical-stimulated acute pain. Naloxone did not block the anti-nociceptive effects of TSS, which showed no participation of the opioid system. We investigated the electrical signal in cultured cortical neurons to explore whether TSS treatment directly affected synaptic transmission. TSS treatment selectively increased spontaneous inhibitory synaptic release and GABA induced charge transfer in mouse cortical neurons. The effects of TSS were maintained for at least 8 h in cultured neurons and in injected mice. Taken together, our results suggest that the analgesic role of TSS in cortex occurs via a particular increase in the inhibitory synaptic response at resting state, which supports TSS as a potential candidate for inflammatory pain relief.